Profil Input Kelas Unggul Pendidikan Dasar dan Menengah di Provinsi Jambi - Hary Soedarto Harjono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Aim of this article is to describe factually profile of excellent class in primary and secondary school at Jambi province. The profile can be used as recommendation for stakeholders to manage excellence schools more precisely. Moreover, from this evaluative research, the results can be used to improve inputs, teaching and learning process, and output of the excellence classroom schools in Jambi province.